Digital-Tropical: Venice of the East - Baharin H.; Abd Manan M.S.; Harun A.F.; Baharuddin N.; Bin Mastro M.H.; Ibrahim N.; Nohuddin P.N.E.; Abdul Shukor S.F. (Association for Computing Machinery, 2023)
Data visualization; Ecosystems; Energy policy; Global warming; Houses; Renewable energy resources; Water waves; Wave energy conversion; Floodings; Light projection; Malaysia; Malaysians; Modular designs; Natural environments; Renewable energy projects; River levels; Uncertainty; Wave heights; Tropics